2019
DOI: 10.1021/acsaem.9b01469
|View full text |Cite
|
Sign up to set email alerts
|

High-Rate and High-Voltage Aqueous Rechargeable Zinc Ammonium Hybrid Battery from Selective Cation Intercalation Cathode

Abstract: The shortage of lithium resources is promoting the development of cost-efficient battery candidates, especially aqueous rechargeable batteries (ARBs) with high safety and power density. Copper hexacyanoferrate (CuHCF) nanoparticles with high redox potential and rate capability is employed as the battery cathode for hosting ammonium-ion coupling with low-cost zinc anode. Benefiting from the selective ammonium-ion channel in CuHCF, an aqueous rechargeable zinc ammonium hybrid battery is successfully engineered. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 42 publications
2
70
0
Order By: Relevance
“…During the initial cycles, heterostructural VS 2 /VO x demonstrates fast capacity decay due to the side reaction and formation of new phases, and then it stabilizes at 150 mA h g −1 and reaches over 120 mA h g −1 after 50 cycles, the highest value among the state‐of‐the‐art materials for NH 4 + ion storage (Figure 4f). [ 16,17,43–48 ] On the contrary, the C–V curves of VS 2 shown in Figure S19, Supporting Information, exhibit inferior reversibility for NH 4 + ion storage, and the reversible capacity is achieved less than 100 mA h g −1 (Figure 5c ; Figure S20, Supporting Information) with a poor coulombic efficiency below 85% during the cycling. The long‐term cycling performance of VS 2 /VO x heterostructure was also recorded at high current density of 1 A g −1 .…”
Section: Resultsmentioning
confidence: 99%
“…During the initial cycles, heterostructural VS 2 /VO x demonstrates fast capacity decay due to the side reaction and formation of new phases, and then it stabilizes at 150 mA h g −1 and reaches over 120 mA h g −1 after 50 cycles, the highest value among the state‐of‐the‐art materials for NH 4 + ion storage (Figure 4f). [ 16,17,43–48 ] On the contrary, the C–V curves of VS 2 shown in Figure S19, Supporting Information, exhibit inferior reversibility for NH 4 + ion storage, and the reversible capacity is achieved less than 100 mA h g −1 (Figure 5c ; Figure S20, Supporting Information) with a poor coulombic efficiency below 85% during the cycling. The long‐term cycling performance of VS 2 /VO x heterostructure was also recorded at high current density of 1 A g −1 .…”
Section: Resultsmentioning
confidence: 99%
“…in 2012, [3] achievements have been made on NH 4 + storage for aqueous energy storage (Figure 1). Ti 3 C 2 MXene, [4] Prussian blue analogues (e.g., sodium iron hexacyanoferrate, [5] copper hexacyanoferrate, [6] berlin green, [7] ammonium Prussian white [2] ), organic solids (e.g., 3,4,9,10‐perylenetetracarboxylic diimide, [2] polyaniline [8] ), and metal oxides (e.g., titanic acid, [9] V 2 O 5 , [10] MoO 3 , [11] NH 4 V 4 O 10 [8] ) were studied to enrich the NH 4 + ‐storage chemistry. For example, Ji et al.…”
Section: Figurementioning
confidence: 99%
“…They also revealed that the NH 4 + intercalation/extraction in Berlin green was of nearly zero strain, thus resulting in enhanced cycling stability as compared with that of the Na + and K + intercalations. [ 119 ] Recently, Huang's group also reported the NH 4 + intercalation in Na‐FeHCF [ 120 ] and Cu‐HCF, [ 121 ] they not only achieved excellent cycling and rate performance via controlling morphologies and sizes of Na‐FeHCF nanocubes, but also revealed the selective NH 4 + channel in CuHCF, which leads to high cell voltage (≈1.8 V) and outstanding rate performance of Zn 2+ /NH 4 + hybrid batteries. In consideration of the high abundance of NH 4 + on earth, further investigations shall be done to develop effective PBA cathode materials for NH 4 + storage, which is of great importance for the development of next‐generation batteries.…”
Section: Prospects On Future Research and Development Of Pba Cathode mentioning
confidence: 99%